ANALISIS PENGETAHUAN IBU TENTANG PEMBERIAN MP-ASI DENGAN BERAT BADAN BAYI DI DESA TAMBAK SOGRA KECAMATAN SUMBANG, KABUPATEN BANYUMAS - Adriani, Prasanti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT : ANALYSIS KNOWLEDGE OF MOTHER ON THE GRANTING OF COMPLEMENTARY BREASTFEEDING WITH WEIGHT INFANTS IN BANYUMAS. Complementary breastfeeding is the transition from breastfeeding transition to feed their families. The introduction of complementary breastfeeding and provision should be made gradually form and amount, according to the baby's or child's digestive ability. Complementary breastfeeding is given from age 4 to 24 months. Increasingly increasing age of the baby or child, growing nutritional needs for growth and development of children, while the milk produced does not meet nutritional needs. This study aims to determine the relationship of the level of knowledge about the baby's mother giving complementary breastfeeding with infant weight change in the Tambak Sogra Village, Sumbang, Banyumas district in 2013. This research is analytic correlation with cross sectional approach. Samples used in this study were mothers of infants who had a baby aged 6 to 24 months. Samples in this study was 30 respondents. The results obtained from 8 respondents with good knowledge of most of the baby weight change was good (34.3%) in saying well if cords following the green line, of the 13 respondents with sufficient knowledge of most of the changes in the baby's weight is enough (55.3%) in saying  enough  if  the  lines  follow  the  yellow  ribbons,  and  from  9  respondents  with  poor knowledge of most of the baby weight change is bad (10.4%) in saying bad if the lines follow the red tape. There is a  level  of  knowledge mother infant  relationships on  giving  complementary breastfeeding with infant weight change.  Key words: Complementary breastfeeding, Infant Weight, Knowledge